Institutional Pressures and Servitization Paradox: The Moderating Effect of Organizational Identity Orientations - Wang, Hui; Lu, Xiaojing; Hu, Chaping; Wang, Haijun (Frontiers in Psychology, 2022)
It is believed in many studies that the servitization of manufactures is driven by internal economy, but the situation in China may be somewhat different. In this study, we consider the influence of external institutional environment on manufacturers' servitization and the final performance, and discuss the moderating effect of organizational identity orientation on firms' response to external institutional pressures. We conduct a survey where we collect responses from 312 manufacturers in China. Regression analyses are performed to test whether institutional pressures (normative pressure, mimetic pressure, and coercive pressure) coming from the external institutional environment have a positive effect on the level of manufacturing servatization or not. Moreover, we study if this positive effect is moderated by the individualistic identity orientation and the relational identity orientation. We also examine the impact of servatization strategy on manufacture’s market performance and financial performances. Furthermore, we separate out the influences comes from institutional pressures by using a new estimated method and try to explain the cause of “servitization paradox”. Our study is innovative in that it bridges the servitization and institutional theory, and provides practical guidance for the adoption of manufacturing servatization strategy.